Pengembangan Kapasitas Pegawai Badan Layanan Umum Daerah Non Pegawai Negeri Sipil (Studi di RSUD Kabupaten Sidoarjo) - Satriya, Ageng; Domai, Tjahjanulin; Setyowati, Endah (FIA UB, 2016)
Capacity Building of Regional Public Service Instance Employees for Non Civil Servants (Study Case in Provincial Hospital Sidoarjo). Capacity building thorugh education has yet to be implemented affectively, especially for Non Civil Servants employees because of the regulations. The Regulations which is indicates that only the Civil Servants Employees who have the rights to obtain education facilities are covered by Government. While for Non Civil Servants employees can obtain rights equal to using the Provincial Hospital Sidoarjo financial. And capacity building also constrained in stage of training evaluation, the evaluation of benefits applies has not been able to walk properly.